Etymology, History and Development of the Semantics of Food Names in Ukrainian Chronicles of the End of the 17th and the Beginning of the 18th Century - Kryzhko, Olena (Slavistica Vilnensis, 2024)
The article examines the etymology, history and semantic development of food names found in late 17th- and early 18th-century Ukrainian chronicles, including those by Samovydetsia, S. Velichko, and H. Hrabianka. Taking a synchronic-diachronic approach, the author analyzes these food nominations within the lexical-semantic domains of generic food names and dish names, establishing semantic relationships such as polysemy, synonymy and variation. This analysis traces the evolution of the Ukrainian language’s lexical composition and reveals its nationally distinct characteristics. By following these food nominations from their earliest written attestations through the period depicted in the chronicles, the study clearly illustrates the semantic development of the given food terminology. The author notes that words of Proto-Slavic origin comprise a significant portion of the food terminology used in late 17th- and early 18th-century Ukrainian chronicles. Borrowings from various languages are also used, including Polish, Old Slavic, Turkic, Russian, and German (occasionally by way of Polish), as well as Italian via German. The presence of these loanwords is explained by key historical events in Ukraine across different periods that shaped the development of the language. Taken together, the linguistic evidence across these chronicles illustrates the codification of a fledgling Ukrainian literary tradition firmly rooted in popular verbal traditions.